دور القوى الإقليمية في إدارة النزاعات بمنطقة القوقاز -دراسة في إقليم ناغورنو كاراباخ- - برق, سميحة (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
The impact of the structural changes that came after the end of the Cold War required the conflict management theorists to pay attention to new mechanisms that enable them to make peace and stop conflicts before it reaches to the level of total war which we tried to make it clear in our study by applying a group of theories and approaches that fits with the variables through the analysis of The conflicting territoriality over the location of the Nagorno-Karabakh region in the South Caucasus, monitoring the various developments in the conflict in the region and identifying the mechanisms used by the actors to achieve their interests. Based on this, it became clear to us that the dynamics causing the conflict within the region are due to a group of factors, including those linked to historical and geographical ethnic hatreds. Externally, they are related to the intervention of regional units in the form of strategic alliances targeting energy resources. This conflict is a common issue between Arminia and Azerbaijan supported by geopolitical alliances and a security trouble governed by ethnic movements. Through this study, the conclusion was reached that the multiplicity of conflict management mechanisms used by official or non-official actors in the region was in order to escalate the intensity of the conflict (frozen conflict) and contribute to make the roles of regional powers great , except for the preventive role pursued by Russia, which led to the launch of The fire and the signing of a tripartite agreement between it and the conflicting parties, but its outcomes were more positive for them than dealing with the situation of the region or studying issues related to the conditions of refugees and displaced persons, At the end of this study, we build a forward-looking vision through the scenario technique as the possibility of the conflict remaining within the current situation by activating the 2020 agreement or the conflict prevention and peace-building scenario by giving the region autonomy or its development to the level of comprehensive war in the South Caucasus in application of the data of the transformational scenario . الملخص: إن تأثير التغييرات البنيوية التي أعقبت نهاية الحرب الباردة استوجبت على منظري علم إدارة النزاعات الاهتمام باليات جديدة تمكنها من بناء السلام ودرء النزاع قبل بلوغه مستوى الحرب الشاملة وهو ما حاولنا توضيحه من خلال دراستنا حيث وظفنا مجموعة من النظريات والمقاربات التي تتلاءم والمتغيرات البحثية عبر تحليل ادوار القوى الإقليمية المتنازعة على موقع إقليم ناغورنو كاراباخ الجيوسياسي في منطقة جنوب القوقاز، رصد مختلف التطورات التي مر بها النزاع في الإقليم وتحديد الآليات المنتهجة من طرف هذه الفواعل لبلوغ مصالحها الجيوسياسية. استنادا إلى ذلك تبين لنا أن الحركيات المسببة للنزاع داخل الإقليم تعود لمجموعة من العوامل الداخلية المرتبطة بالأحقاد التاريخية، الجغرافية العرقية والمطالبة بالحقوق المجتمعية للأقلية الأرمينية، أما على المستوى الخارجي فتتعلق بتدخل الوحدات الإقليمية في شكل تحالفات إستراتيجية تستهدف الموارد الطاقوية، فهذا النزاع يصنف ضمن الصراعات الخامدة التي تنفجر عندما تريد هذه الفواعل تحقيق هدف ما، من قبيل اعتباره أزمة بينية مشتركة بين أرمينيا وأذربيجان تدعمها التحالفات الجيوسياسية تحكمها المباريات الصفرية وكمأزق امني مجتمعي تحكمه الحركات العرقية والذي غالبا ما تحقق فيه أذربيجان التفوق اللوجيستي بدعم تركي إسرائيلي مقابل أرمينيا التي تسجل خسائر كبيرة رغم الدعم الروسي الإيراني الخفي. ولقد تم التوصل من خلال هذه الدراسة لنتيجة مفادها أن تعدد آليات إدارة النزاع المنتهجة من قبل الفواعل الرسمية أو غير الرسمية في الإقليم كانت من اجل تصعيد حدة النزاع(الصراع المجمد) والمساهمة في تعظيم ادوار القوى الإقليمية (الدول المتنافسة تركيا، روسيا) باستثناء الدور الوقائي الذي انتهجته روسيا والذي أضفى لوفق إطلاق النار وتوقيع اتفاق ثلاثي بينها وبين الأطراف المتنازعة لكن مخرجاته كانت ايجابية بالنسبة للجانب الروسي أكثر من معالجة وضع الإقليم أو دراسة المسائل المتعلقة بأوضاع اللاجئين والنازحين، لنبني في نهاية هذه الدراسة تصورا إستشرافيا عبر تقنية السيناريو مكنتنا من احتمال إمكانية بقاء النزاع مجمد بفعل الاتفاقية السارية المفعول منذ2020 أو سيناريو منع النزاع وبناء السلام من خلال إعطاء الإقليم الحكم الذاتي والاهتمام بوضع الإقليم أو تطوره لمستوى الحرب الشاملة داخل منطقة جنوب القوقاز وفقا للسيناريو التحولي.
أطروحة دكتوراه تخصص إستراتيجية وعلاقات دولية في الحقوق و العلوم السياسية
Keywords: عربيّــة: إدارة النزاعات، إقليم ناغورنو كاراباخ، جنوب القوقاز، القوى الإقليمية، بناء السلام.; conflict management، Nagorno-Karabakh region، the South Caucasus،regional forces peace-building,.